Controversies in the Management of Gynecological Cancers - Ledermann, Jonathan A.; Creutzberg, Carien L.; Quinn, Michael A. (Springer London : Imprint: Springer, 2014)
Gynecological cancers are some of the most commonly occurring malignancies in women. Despite their high incidence, treatment and management of these cancers remain controversial, with conflicting evidence about  many aspects of the disease.   Controversies in the Management of Gynecological Cancers offers a unique assessment of the opposing sides of the controversial issues associated with gynecological cancers, and aims to provide professionals in the field with a keener sense of the underlying evidence-base and a starting point from which to follow the ongoing debate. A section on the direction of future research to resolve these issues completes the discussion in each chapter.   This book will appeal to specialists, trainees and healthcare workers in gynecological oncology, gynecologists, medical oncologists and radiation oncologists, and is an excellent starting point for anyone who wishes to gain a better understanding of the complex nature of the management of gynecological malignancy.  .